Kajian Fitokimia dan Identifikasi Senyawa Metaboli Sekunder Daun Pare (Momordica Charantia L.) - Taupik, Muhammad; Nurrohwinta Djuwarno, Endah; Adam Mustapa, Moh (Al-Kimia, 2021)
Pare plant is a plant that is found in almost every region in the country Indonesia. Plant is used as a traditional medicine to eliminate some diseases. The aim of this study was to isolate and identify the compounds terpenoids methanol extract fraction of n-hexane pare leaf (Momordica charantia L.) using UV-VIS spectrophotometry. Insulation done by maceration method using methanol to produce condensed methanol extract as much as 36.25 grams. Extracts condensed methanol produced is tested phytochemical. Phytochemical test results shows that it contains alkaloids, saponins and steroid / terpenoids. Condensed methanol extract then fractionated using liquid-liquid partition with solvent n-hexane and methanol with a ratio of 4: 2 ie 133 ml of n-hexane and 67 mL of methanol. Non-polar phase (phase n-hexane) results of further partitioning is evaporated using a rotary evaporator to produce a thick n-hexane extract as much as 1.25 grams hereinafter in the TLC test ratio of solvent to produce the best. Solvents are chosen that n-hexane: ethyl acetate (3: 1). Separation and purification was performed using Vacuum Liquid Chromatography (KCV) using silica gel GF254 as stationary phase and solvent n-hexane: methanol as mobile phase and eluted gradually. Isolates were then tested using Thin Layer Chromatography (TLC). Isolates were identified using UV-VIS spectrophotometry. Analysis of physicochemical data qualitatively using UV-VIS spectrophotometry on samples of the methanol extract of N-Hexane fraction pare leaf (Momordica charantia L.) class of compounds containing triterpenoids. This is because the absorption band at a wavelength of 274.2 nm and 432.8 nm with absorbance respectively 0.601 and 0.177 were suspected because of the transition of an electron from n à π*.